ESTUDO DE CASO DE PACIENTE COM ADENOCARCINOMA DE PULMÃO: UM RELATO DE EXPERIENCIA - Freire, Maria R. A.; Barasuol, Mônica E. C.; Klein, Rubia N.; Kolankiewicz, Adriane C. B. (Salão do Conhecimento, 2013)
Resumo